Creating personal presence look, talk, think, and act like a leader - Booher, Dianna Daniels (San Francisco Berrett-Koehler Publishers, 2011)
It may be difficult to define, but we all know presence when we encounter it. Someone walks into the room and people step aside. Heads turn. When those with presence speak, people listen. When they ask, people answer. When they lead, people follow. People with presence look confident and comfortable, speak persuasively, think clearly even under pressure, and act with intention and integrity.
Includes bibliographical references and index.
Keywords: Leadership--Psychological aspects